Gender Issues in Microfinance and Repayment Performance: The Case of a Nicaraguan Microfinance Institution. - Saravia-Matus, Silvia; Saravia-Matus, Jimmy (Encuentro, 2012)
As a result of some spot observations conducted on Managua, capital city of Nicaragua, a preliminary list of mollusks and birds was published. The list was made up of 18 species, 12 families and three orders of mollusks as well as 41 species, 23 families and 9 orders of birds. These values are consistent with total species numbers estimated by experts on these taxa for the country. This was the first inventory from these taxa associated to the city of Managua, where previous data on trees already existed. These results are analyzed in the light of existing literature on the subject.